2008
DOI: 10.1016/j.neurobiolaging.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain and behavior changes in 12-month-old Tg2576 and nontransgenic mice exposed to anesthetics

Abstract: Inhaled anesthetics have been shown to increase the aggregation of amyloid beta in vitro through the stabilization of intermediate toxic oligomers, which are thought to contribute to neurocognitive dysfunction in Alzheimer's disease. Inhaled anesthetics may escalate cognitive dysfunction through enhancement of these intermediate oligomer concentrations. We intermittently exposed 12-month-old Tg2576 transgenic mice and nontransgenic littermates to isoflurane and halothane for 5 days. Cognitive function was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
192
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 43 publications
8
192
1
1
Order By: Relevance
“…A pilot study in 7-day-old rats (n ϭ 20) confirmed a success rate of intracerebroventricular injection of 100% (data not shown). After xestospongin C administration, rats were exposed to 1% (n ϭ 8) or 1.5% (n ϭ 10) isoflurane for 6 h in a chamber as described previously (Li et al, 2007;Bianchi et al, 2008). Control rats at P7 in the vehicle-only group (n ϭ 10) received the same amount of normal saline but without the addition of xestospongin C. The isoflurane concentration in the chamber was monitored and maintained by using a vaporizer.…”
Section: Animal Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A pilot study in 7-day-old rats (n ϭ 20) confirmed a success rate of intracerebroventricular injection of 100% (data not shown). After xestospongin C administration, rats were exposed to 1% (n ϭ 8) or 1.5% (n ϭ 10) isoflurane for 6 h in a chamber as described previously (Li et al, 2007;Bianchi et al, 2008). Control rats at P7 in the vehicle-only group (n ϭ 10) received the same amount of normal saline but without the addition of xestospongin C. The isoflurane concentration in the chamber was monitored and maintained by using a vaporizer.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Rats exposed at day P7 were allowed to mature before Morris water maze (MWM). Testing of spatial learning and memory was performed in the MWM with protocols and paradigms as previously described (Li et al, 2007;Bianchi et al, 2008). In brief, experimental and control P35 rats were trained to locate an escape platform (1.5 cm in diameter) within a fiberglass pool (1.5 m in diameter) by distant visual cues located on the walls around the pool and a pole with flags on the escape platform.…”
Section: Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…114,133 In addition to the Aβ-anesthesia connection, Xie's group has utilized human neuroglioma cell cultures to add DOI:10.1002/MSJ anesthesia-induced apoptosis as a factor contributing to AD. 114,134 -136 Do the rodent and cell-culture findings apply to humans?…”
Section: Anesthesia and Neurodegenerative Diseasesmentioning
confidence: 99%